Revision der nearktischen und neotropischen Epermeniidae (Lepidoptera). - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1977)
This revision of the Epermeniidae of the Nearctic and Neotropical regions is based of the study of extensive material. Of the twelve taxa known so far, eleven could by examined. Three were revealed as synonyms, two taxa had to be transferred to other genera. Five taxa are described as new species, two of them belonging to a new genus. Nomenclatural Actsalameda Braun, 1923 (Epermenia), syn. n. of Epermenia (Calotripis) cicutaella Kearfott, 1903bidentata Braun, 1926 (Epermenia), syn. n. of Ochromolopis ramapoella (Kearfott, 1903)metrothetis Meyrick, 1921 (Epermenia), syn. n. of Ochromolopis ramapoella (Kearfott, 1903)californica Gaedike, 1977 (Epermenia (Calotripis)), spec. n.lomatii Gaedike, 1977 (Epermenia (Calotripis)), spec. n.stolidota (Meyrick, 1917) (Epermenia (Calotripis)), comb. n. hitherto Acanthedra stolidotastrictelloides Gaedike, 1977 (Epermenia (Calotripis)), spec. n.Acanthedra Meyrick, 1917 (Epermeniidae), syn. n. of Epermenia Hübner, 1825Epimenia Kearfott, 1903 (Epermeniidae), syn. n. of Epermenia Hübner, 1825Parochromolopis Gaedike, 1977 (Epermeniidae), gen. n.ramapoella (Kearfott, 1903) (Ochromolopis), comb. n. hitherto Epimenia [sic!] ramapoellafloridana Gaedike, 1977 (Parochromolopis), spec. n.parishi Gaedike, 1977 (Parochromolopis), spec. n.syncrata (Meyrick, 1921) (Parochromolopis), comb. n. hitherto Epermenia syncrata